Assessing the fall risk with Stay Independent Questionnaire in people with stroke - Chen, Peiming; Liu, T. W.; Ng, Shamay S. M. (Frontiers in Neurology, 2025)
ObjectivesThis study aimed to assess the psychometric properties of the Chinese version of the Stay Independent Questionnaire (C-SIQ) in evaluating individuals with stroke.DesignThe study adopted a cross-sectional design.SettingThe research was conducted at a university-based neurorehabilitation center.ParticipantsThe study included a total of 100 individuals with stroke and 49 healthy older adults.MethodsOn Day 1, both individuals with stroke and healthy older adults underwent assessments using the C-SIQ. Additionally, individuals with stroke were evaluated using the Fugl–Meyer Assessment of Lower Extremity (FMA-LE), ankle dorsiflexion and plantarflexion strength, Berg Balance Scale (BBS), Timed-Up and Go Test (TUG), 10-meter walk test (10 mWT), Activities-specific Balance Confidence (ABC) Scale, Stroke Impact Scale (SIS), and Community Integration Measure (CIM). On Day 2 (7 days after Day 1), individuals with stroke were reassessed using the C-SIQ.ResultsIndividuals with stroke exhibited a higher C-SIQ score (6.22 ± 2.98) compared to healthy older adults (1.59 ± 2.01). The C-SIQ demonstrated good test–retest reliability (intraclass correlation coefficient = 0.847) and internal consistency (Cronbach’s alpha = 0.709). The Minimal Detectable Change in C-SIQ score was calculated as 3.05. Exploratory factor analysis revealed four factors with eigenvalues ≥1.0, explaining 57.17% of the total variance. The C-SIQ score exhibited significant correlations (ranging from −0.553 to 0.362) with completion times of the TUG and 10 mWT, FMA-LE, BBS, ABC, SIS, CIM score, paretic ankle dorsiflexion strength, and 6 mWT distance. A cut-off score of 2.5 was identified as the optimal threshold for discriminating fall risk between individuals with stroke and healthy controls.ConclusionThe C-SIQ emerges as a reliable and valid tool for evaluating fall risk in individuals with stroke, showcasing strong correlations with key measures such as TUG times, 10 mWT, FMA-LE, BBS, ABC, SIS, CIM score, paretic ankle dorsiflexion strength, and 6 mWT distance. The C-SIQ demonstrated good test–retest reliability and internal consistency. Exploratory factor analysis revealed that this is a four factors assessment tool. The identified cut-off score of 2.5 effectively distinguishes fall risk between individuals with stroke and healthy controls.